Improving service reusabilty using enterprise service bus and business process execution language - Jaafar, Ako Abubakar (2013)
Despite the ability of current technologies to integrate different applications together, it also makes integrating application and systems more complicated due to poor reusability and coupling in the present technologies. The integration solution of a traditional enterprise application usually focuses on point to Point (P2P) integration. Generally, this type of integration creates tight coupling and complex integration. Service Oriented Architecture (SOA) based integration application is the most current solution which transforms IT systems into highly reusable and loosely coupled services. Web Services are the most prominent and experienced technology under SOA's flag. But using Web Services in SOA-Based integration alone still provides P2P integration. The middleware Enterprise Service Bus (ESB) and orchestration language Business Process Execution Language (BPEL) together can provide loosely coupled and reusable integration. Web Services and ESB/BPEL have different level of reusability. Consequently, this study attempts to investigate the reusability level of ESB/BPEL as compared to Web Services. The evaluation of ESB/BPEL and Point to Point Web Services (P2PWS) has been conducted using the Islamic Banking System integration case study. The implementation services were examined and evaluated using quality model metrics to exhibit the reusability level of ESB/BPEL and P2PWS. Besides the reusability level, the response time of the two approaches have been measured to illustrate architecture impact on performance. The result shows that the ESB/BPEL had a higher level of reusability but poor response time as compared to P2PWS.